Report on Electroencephalographic Findings in Critically Ill Patients with COVID‐19. Issue 3 (9th July 2020) - Vespignani, Hervé; Colas, Damien; Lavin, Bruce S.; Soufflet, Christine; Maillard, Louis; Pourcher, Valérie; Paccoud, Olivier; Medjebar, Samir; Frouin, Pierre‐Yves
Abstract : In March 2020, we treated a cohort of 26 critically ill hospitalized SARS‐CoV‐2–infected patients who underwent electroencephalography to assess unexplained altered mental status, loss of consciousness, or poor arousal and responsiveness. Of the 26 patients studied, 5 patients had electroencephalograms that showed periodic discharges consisting of high‐amplitude frontal monomorphic delta waves with absence of epileptic activity. These findings may suggest central nervous system injury potentially related to COVID‐19 in these patients. ANN NEUROL 2020;88:626–630